2005
DOI: 10.1103/physrevlett.94.168001
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and Competition between Disorder and Crystallization in Sheared and Vibrated Granular Flow

Abstract: Experiments on spherical particles in a 3D Couette cell vibrated from below and sheared from above show a hysteretic freezing/melting transition. Under sufficient vibration a crystallized state is observed, which can be melted by sufficient shear. The critical line for this transition coincides with equal kinetic energies for vibration and shear. The force distribution is double-peaked in the crystalline state and single-peaked with an approximately exponential tail in the disordered state. A linear relation b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 21 publications
3
70
1
Order By: Relevance
“…Though crystallization under shearing is well documented in MD simulations [7,8], a recent experiment [23] showed that, under certain conditions, shearing can lead to disorder.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Though crystallization under shearing is well documented in MD simulations [7,8], a recent experiment [23] showed that, under certain conditions, shearing can lead to disorder.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Important non equilibrium effects of structurally disordered granular systems, beside the slow relaxation to equilibrium [12,22,23], are : bistability and hysteresis [24,25,26] as the result of a memory effect due to the internal history dependence of systems out of equilibrium and the lack of an unique metastable state [2] ; and a jerky response to the external driving force with impulselike events (local rearrangements of grains or avalanches), as the result of the exploration of local minimal energy configurations [27,28]. A related important question is whether a diverging length-scale exists on the jammed side of the transition [29].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the effect of heating or cooling on the phase behavior of a system, vibration can often lead to ordering. 14 In fact, the existence of dynamical and spatial heterogeneities should properly be regarded as a clear consequence of the athermal nature of granular media.…”
Section: Tops Middles and Bottomsmentioning
confidence: 99%